Simulasi Injeksi Anggaran Program Makan Bergizi Gratis serta Dampaknya terhadap Perekonomian Indonesia : (Analisis Input-Output) - Sabrina Do Miswa; Candra Kurniawan (BESTARI BPS Kalimantan Timur, 2025)
This study analyzes the economic impact of the Free Nutritious Meal (MBG) Program budget injection policy in Indonesia using an input-output (IO) model. Simulations were conducted across 17 economic sectors under four budget distribution scenarios, focusing on Sector A (Agriculture, Forestry and Fisheries) and Sector C (Processing Industry). The results indicate that each scenario produces different effects on output, gross value added (GVA), income, and employment. The scenario with the largest allocation to Sector C significantly boosts its output but is less optimal in the long run. Conversely, scenarios allocating more funds to Sector A generate broader impacts on food security and employment absorption. Policy implications include optimizing MBG budget distribution, providing incentives for farmers and food SMEs, and strengthening food infrastructure and supply chains. Additionally, integrating the MBG program with sustainable food security strategies and nutrition education is essential to enhance its effectiveness. With the right approach, the MBG program can contribute to food security, economic well-being, and the achievement of sustainable development goals in Indonesia.